Functional role for Taz during hindbrain ventricle morphogenesis. - Renée Dicipulo; Lyndsay G Selland; Rowan G Carpenter; Andrew J Waskiewicz (PLoS ONE)
The brain ventricle system, composed of the ventricular cavities and the cerebral spinal fluid within, performs critical functions including circulation of nutrients, removal of wastes, and cushioning of neural tissues. Development of the hindbrain ventricle requires a series of factors that coordinate its initial formation and subsequent inflation. Previous work has demonstrated that the transcriptional co-activator Taz (also known as WW domain-containing transcription regulator protein 1, Wwtr1), a component of Hippo signalling, is active at hindbrain rhombomere boundaries where it is regulated by mechanotransduction and promotes proliferation. Here, we demonstrate that Taz is also a critical regulator of hindbrain ventricle development. Zebrafish embryos that lack Taz protein fail to undergo initial midline separation of the hindbrain ventricle. Furthermore, the ventricle phenotype is a result of disorganized cytoskeletal F-actin and apicobasal polarity components. In addition, we have demonstrated that the hindbrain rhombomere boundaries are a location of active Wnt-Hippo crosstalk. Through our work, we propose a model where Taz protein is stabilized at rhombomere boundaries and promotes proper cell polarity necessary for formation of the brain ventricle.